The Relationship Analysis of e-Government Implementation on Increasing Capital Investment in Region (Case Study : Banyuwangi City) - Beny Prasetyo; Tony Dwi Susanto (Institut Teknologi Sepuluh Nopember, 2017)
In recent years, the investment climate in Indonesia is increasing, where the realization of capital investment projects in the first quarter of 2014 reached IDR, 106.6 trillion. The increased capital investment can not be separated from the investment attractiveness in Indonesia. Some traditional factors are labor, infrastructure, ecoonomic, social and political, while ICT factor which have influenced on shaping investment attractiveness is e-government of host country. This research will analyze the relationship between e-government implementation at local government level (city) as one of the strategies to realize good governance. With good governance will influence the investors to come for invest. To answer this research, researcher used a qualitative approach with a single case study is Banyuwangi City in East Java Province, Indonesia. Case study used to explore more details about this research topic. The results of this study are e-government implementation have impact on the improvement of good governance quality and increasing investment value.